Desenvolvimento farmacotécnico de suspensão oral reconstituída contendo complexo furazolidona: ?-ciclodextrina - Siqueira, Larissa Ataide (2018)
Canine cutaneous leishmaniasis (LCC) is an infectious disease, caused by a protozoan of the genus Leishmania, vector transmission, which affects skin and mucosa. It is considered a zoonosis that affects animals and men. There is currently no pharmacotherapy available for the treatment of LCCin Brazil. Thus, the search for pharmaceutical alternatives for use in animals has been the subject of numerous researches. The leishmanicidal activity of furazolidone has been studied by several authors and, since the drug is not used in the treatment of leishmaniasis in man, its use for the treatment of LCCcan be considered. In this sense, the objective of the present work was to continue the research developed by the group with a view to developing a new medicine to treat cutaneous leishmaniasis in dogs. In the present stage of the work, the pharmacotechnical development of a reconstituted oral suspension containing the furazolidone: ß-cyclodextrin complex prepared in the ratio 1: 2 and obtained by malaxation was proposed. Initially, structured carriers containing sodium carboxymethylcellulose as suspending agent were prepared in concentrations 0.3%, 0.4%, 0.5% and 0.6% w / v. Flavoring veterinary use of bacon flavor was used to tailor the flavor of the formulation to the palate of dogs. The vehicles had pH, viscosity and rheological behavior studied. The complex was then incorporated into the formulations, which were tested for physical stability, namely, pH, particle size, zeta potential, sedimentation rate and reconstitution time. Finally, for the determination of the drug content in the suspension, a spectrophotometric assay method in the ultraviolet region was validated. The vehicle having the best viscosity was the one containing 0.5% w / vof the thickener, and the rheological behavior observed was that of a non-Newtonian pseudoplastic fluid, adequate to the requirement of the suspensions. The dispersion index obtained for the particles was 3.68 and the system can be considered polydispersed, which was confirmed by the analysis by scanning electron microscopy. The mean particle size was less than 10 11µm and the zeta potential of the suspension at pH 6.0 was -59 mV, and the system could be considered flocculated. The suspension presented adequate sedimentation volume and a small redispersion time, and the formation of rigid agglomerates was not observed, which contributes to the uniformity of doses. Finally, the proposed assay method showed to be specific, linear, accurate, precise and robust, and can be safely used for the dosing of the complexed drug in the reconstituted oral suspension. The drug content was 104.7%. Considering that pharmaceuticals should contain from 90 to 110% of the active principle declared on their labels to be consideredchemically stable, the formulation met this requirement